2020
DOI: 10.1021/acs.macromol.0c01276
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Oxygenated Block Copolymers by Polymerization of Epoxides and Lactide Using Cationic Indium Complexes

Abstract: Cationic indium complexes were used as catalysts for the copolymerization of epoxides and racemic lactide (rac-LA) via sequential addition to form high-molecular weight block copolymers. Mechanistic studies and control experiments indicate that the epoxide is polymerized by a cationic mechanism to yield a neutral alkoxide indium species that subsequently polymerizes the lactide by a coordination-insertion mechanism with no significant interference of the two mechanisms under polymerization conditions. The ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 79 publications
(114 reference statements)
0
15
0
Order By: Relevance
“…46−48 Moreover, the 31 P nuclei can serve as probes to study the behavior of complexes in situ by using 31 P{ 1 H} NMR spectroscopy. For example, Li and co-workers used 31 alkyl complexes during the polymerization of ε-caprolactone G. 49 We have been studying 50 neutral and cationic indium complexes as catalysts for the controlled ring-opening polymerization of cyclic esters 51−55 and epoxides 56,57 as well as the copolymerization of lactones and acrylates 58 and coupling of lactones and epoxides to form spiroorthoesters. 59 We showed that introducing hemilabile thiophene, furan, and pyridine donors in series of complexes H can have a profound impact on catalyst stability and reactivity for the polymerization of epichlorohydrin, cyclohexene oxide, and rac-lactide.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…46−48 Moreover, the 31 P nuclei can serve as probes to study the behavior of complexes in situ by using 31 P{ 1 H} NMR spectroscopy. For example, Li and co-workers used 31 alkyl complexes during the polymerization of ε-caprolactone G. 49 We have been studying 50 neutral and cationic indium complexes as catalysts for the controlled ring-opening polymerization of cyclic esters 51−55 and epoxides 56,57 as well as the copolymerization of lactones and acrylates 58 and coupling of lactones and epoxides to form spiroorthoesters. 59 We showed that introducing hemilabile thiophene, furan, and pyridine donors in series of complexes H can have a profound impact on catalyst stability and reactivity for the polymerization of epichlorohydrin, cyclohexene oxide, and rac-lactide.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We have been studying neutral and cationic indium complexes as catalysts for the controlled ring-opening polymerization of cyclic esters and epoxides , as well as the copolymerization of lactones and acrylates and coupling of lactones and epoxides to form spiroorthoesters . We showed that introducing hemilabile thiophene, furan, and pyridine donors in series of complexes H can have a profound impact on catalyst stability and reactivity for the polymerization of epichlorohydrin, cyclohexene oxide, and rac -lactide …”
Section: Introductionmentioning
confidence: 99%
“…Stereoregular PLAs are crystalline polymers with a high melting point, whereas atactic PLA is amorphous and brittle. Therefore, extensive efforts have been focused on the synthesis of stereoregular PLAs, [ 4‐5 ] and a variety of catalysts/initiators have been applied in the controlled ROP of rac ‐LA, including organocatalysts, [ 6‐8 ] main group metal, [ 9‐17 ] transition metal, [ 18‐20 ] and rare earth metal complexes. [ 21‐23 ] Among them, rare earth metal complexes have attracted intensive attention due to their high activity, high stereoselectivity, and good controllability for polymerization under mild conditions.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…40 kg/mol with relatively narrow dispersity (Đ < 1.3). [49][50][51] This system also effectively copolymerized ECH with THF, oxetane, oxepane, and lactide to make some interesting copolymers.…”
Section: Cationic Ring Opening Polymerization Of Echmentioning
confidence: 99%